Patient Safety Problems Associated with Heathcare Information Technology: an Analysis of Adverse Events Reported to the US Food and Drug Administration - Magrabi, Farah (American Medical Informatics Association, 2011)
The objective of this paper is to analyze healthcare information technology (HIT) events associated with patient harm submitted to the US Food and Drug Administration (FDA) Manufacturer and User Facility Device Experience (MAUDE) database. We examined the problems in 46 relevant events submitted to MAUDE from January 2008 to July 2010 to identify natural categories of problems from a clinical perspective. CPOE and PACS were involved in 93% of the events. Adverse events were associated with medications in 41%, clinical processes in 33%, radiation in 15% and surgery in 11%. There were four deaths. Strategies to improve the safety of HIT should focus on designing safe user interfaces, integrated checks of key identifiers and decision support, and engineering safer clinical processes.